POTENSI EKSTRAK KENTANG HITAM (Coleus tuberosus) SEBAGAI ANTIOKSIDAN DAN ANTI-PROLIFERASI SEL KANKER PAYUDARA (MCF-7) IN VITRO - , Mutiara Nugraheni, Prof. Dr. Ir. Umar Santoso, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The human body every day always exposed to free radicals which come from exogenous or endogenous the body. Although the body antioxidant defense systems exist, but the body can happen oxidative stress in case of an imbalance between the amount of antioxidants and reactive oxygen species. Oxidative stress that occurs in the body can result in degenerative diseases, such as breast cancer. One effort to increase the antioxidants in the body is by consuming foods that contain bioactive compounds that can reduce the risk of cancer. Plants that potentially increase the antioxidants in the body is Coleus tuberosus. Coleus tuberosus may contain bioactive compounds, such as triterpenic acid. However, information on the type and amount of triterpenic acid in different parts of the Coleus tuberosus, and its relation with its potential as an antioxidant and antiproliferative still unknown. The purpose of this study was to determine the content of triterpenic acid (oleanolic acid and ursolic acid) from several parts of Coleus tuberosus (peel nand flesh)